Dark winds. Season 3 [videorecording (DVD)] - Hillerman, Tony; McClarnon, Zahn, 1966-; Gordon, Kiowa, 1990-; Matten, Jessica; Allison, Deanna (AMC Studios, 2025)
The third season of Dark Winds follows Lt. Joe Leaphorn and Jim Chee as they investigate the disappearance of two boys. Meanwhile, Bernadette Manuelito attempts to settle into her new life, but stumbles across a conspiracy with far-reaching implications.